Review of Key Technologies of mobile energy storage vehicle participating in distribution network dispatching under the high proportion of renewable energy access. Issue 1 (1st October 2022) - Li, Wenpei; Xiang, Bin; Xiong, Hu; Li, Jiayuan; Yang, Fan
Abstract: With modern society's increasing reliance on electric energy, rapid growth in demand for electricity, and the increasingly high requirements for power supply quality, sudden power outages are bound to cause damage to people's regular order of life and the normal functioning of society. Currently, the commonly used emergency power protection equipment is mainly based on diesel generator sets, while there is also flywheel energy storage equipment in the application of emergency power protection. In today's society, we strongly advocate green, energy-saving, and emission reduction background, and the demand for new mobile power supply systems becomes very urgent. Mobile energy storage vehicles can not only charge and discharge, but they can also facilitate more proactive distribution network planning and dispatching by moving around. The basic model and typical application scenarios of a mobile power supply system with battery energy storage as the platform are introduced, and the input process and key technologies of mobile energy storage devices under different operation modes are elaborated to provide strong support for further input and reasonable dispatch of mobile energy storage vehicles.